Pengaruh Model Pembelajaran RADEC terhadap Perubahan Penguasaan Konsep Siswa Sekolah Dasar Materi Siklus Air - Novi Ratnasari; Wati Sukmawati (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The research objective was to see changes in elementary school students' mastery of the concept of the water cycle using the RADEC model. This study uses a quantitative method with true experimental pre test-post test control group design. Based on the research results, score mean pre test and post test Mastery of concepts using the RADEC model achieves a score of 62 for pre test and 79 for post test. Meanwhile, using the conventional model achieved a score of 66 for pre test and 77 for post test. This shows that the use of the RADEC model makes a significant change in students' mastery of concepts.